Forecasting the Recovery from the Great Recession: Is This Time Different? - Dominguez, Kathryn M. E; Shapiro, Matthew D (American Economic Review, 2013)
This paper asks whether the slow recovery of the US economy from the trough of the Great Recession was anticipated, and identifies some of the factors that contributed to surprises in the course of the recovery. We construct a narrative using news reports and government announcements to identify policy and financial shocks. We then compare forecasts and forecast revisions of GDP to the narrative. Successive financial and fiscal shocks emanating from Europe, together with self-inflicted wounds from the political stalemate over the US fiscal situation, help explain the slowing of the pace of an already slow recovery.